Possible requirement of executive functions for high performance in soccer - Sakamoto, A.; Takeuchi, H.; Ihara, N.; Ligao, B.; Suzukawa, K. (PLOS ONE, 2018)
In open-skill sports such as soccer, the environment surrounding players is rapidly changing. Therefore, players are required to process a large amount of external information and take appropriate actions in a very short period. Executive functions (EFs)—the cognitive control processes that regulate thoughts and action—are needed for high performance in soccer. In this study, we measured the EFs of young soccer players aged 8-11 years, who were applying for admission to an elite youth program of a Japanese Football League club. We found that even though admission was determined by the soccer performance of the players, significant differences were observed between players who were approved and those who were not approved into the program. Soccer players who had been approved into the program got higher scores in general EFs tests than those who had been rejected. Our results proposed that measuring EFs provides coaches with another objective way to assess the performance levels of soccer players.